Zolpidem Action During Prolonged Disorders of Consciousness (Case Report) - E. A. Kondratyeva; M. V. Sinkin; E. V. Sharova; S. Laureys; A. N. Kondratyev (Общая реаниматология, 2019)
The paper describes two patients with prolonged disorders of consciousness (PDC) because of non-traumatic brain injury, in whom a clear neurodynamic response to Zolpidem was observed.In order to illustrate systemic cerebral responses to administration of this drug in LIC patients, an analysis of clinical and electrophysiological changes has been undertaken.It has been shown that the result of Zolpidem applications in patients with prolonged disorders of consciousness (PDC) should be assessed not only by consciousness dynamics, but with the help of electroencephalogram (EEG) monitoring, too. Distinct response to Zolpidem during different periods of recovery in one patients was found.Zolpidem can render various effects in patients in vegetative state/with unresponsive wakefulness syndrome (VS/UWS) and in minimally conscious state (MCS). In one patient, sedation with EEG activation was observed, which was a sign of favorable prognosis. The other patient developed more than once local convulsions after Zolpidem administration followed by contact augmentation on the next day.The mechanism of action, necessary doses of drugs, and markers of forecasting the successful effect of that drug are yet to be further studied.